Efeito do treinamento intervalado de alta intensidade na composição corporal, na regulação do processo inflamatório e do metabolismo de ratos Wistar alimentados com dieta hiperlipídica - Costa, Leandro Ribeiro (2017)
This study aims to analyze the behavior of Omentin and Vaspin in relation to a high intensity interval training protocol (HIIT) in rats fed a hyperlipidic diet. To this end, male Wistar rats, divided into 4 groups, received standard or high fat diet depending on the group for 4 weeks. After the induction to body fat gain, the training protocol began, with duration of 10 weeks, divided in 2 weeks of adaptation and 8 of HIIT. The animals in the trained groups performed 3 training sessions per week. Body mass and food intake were measured daily. At the end of the experimental period euthanasia occurred by decapitation, 48 hours after the last training session. Blood was collected and the tissues: gastrocnemius muscle, liver, epididimal white (EPI), retroperitoneal (RET) and visceral (VIS) adipose tissue were removed and immediately weighed. Serum concentrations of the cytokines TNF-α, IL-6, PCR, IL-L8, IL-10, IL-4 and adipokines omentin, vaspin and adiponectin were determined by ELISA and protein expression of omentin and vasin by Western blotting . The results are expressed in mean and standard deviation, the statistical comparisons were made through analysis of variance, and p <0.05 was considered to denote statistical significance. The results demonstrated that the hyperlipid diet protocol is able to promote a significant gain of body fat in 4 weeks, besides promoting, at the end of the experiment, an increase in serum levels of vasin and triglycerides. On the other hand, the high-intensity interval training was able to improve the animals' maximum exercise capacity and to slow the increment of the fat gain. However, training promoted an increase in total cholesterol levels and a reduction in serum adiponectin levels in IL- 10. Thus, the research supports the evidence that high-intensity interval training is able to mobilize fat significantly in a population with excess body fat, however, due to suppression of adiponectin and IL-10 levels, this may not be the ideal protocol for this population in such circumstances and we reinforce the use of vaspin as a biomarker for obesity.